Neo-Keynesian Disequilibrium Theory in a Monetary Economy - Benassy, Jean-Pascal (Review of Economic Studies, 1975)
K-equilibrium concept 3/ The existence of a K-equilibrium V -EFFICIENCY PROPERTIES OF K-EQUILIBRIUM 1/ The criterion 2/ Properties of a K-equilibrium 3/ Inefficiency and multiplier effects 4/ The cause of inefficiency VI -AM EXA/vlPLE 1/ The economy 2/ Computation of equilibrium transactions